Robert Beale, Charles Hallé: A Musical Life (2007) - Palmer, Fiona M. (Journal of the Society for Musicology in Ireland, 2009)
A review of Robert Beale, Charles Hallé: A Musical Life (Aldershot: Ashgate, 2007), ISBN 978-0-7546-6137-5